Health Beyond Health: Insights and Implications from the Fourth National Health Summit of Nepal, 2024 - Jay Bhushan Jha; Anil Bikram Karki; Sanjeeb Tiwari (Journal of Nepal Medical Association)
The 4th National Health Summit in Nepal, themed "Health Beyond Health," explored the interconnections between health and social, economic, and environmental factors, emphasizing the role of health as a driver of national progress. The summit brought together diverse stakeholders, including policymakers, healthcare professionals, researchers, and civil society leaders, to address transformative health strategies. With subthemes ranging from universal health coverage to the impact of climate change on health, the event highlighted the importance of a holistic, intersectoral approach to health system strengthening. This viewpoint reflects on the summit's outcomes, its inclusive and participatory approach, and the critical need for translating recommendations into actionable strategies to achieve health equity and resilience for Nepal's future.